Effect of artificial insemination and natural mating on reproductive parameters in pigs of warm-humid climate region - PACHECO, EDSON BRODELI FIGUEROA; ADEGBEYE, MOYOSORE JOSEPH; LAGUNAS, BLAS CRUZ; SALAS, JOSÉ MANUELCASTRO; AGUILAR, ALEJANDRO SOTELO; HEVERASTICO, CESARIO CATALÁN (The Indian Journal of Animal Sciences, 2020)
Artificial insemination is a popular assisted reproductive technology that ensures transfer of genetic information from animal to animal. This study was meant to evaluate the influence of artificial insemination and natural mating on selected reproductive parameters. Five hybrid females of Duroc-landrace line were selected while 3 boars were used for the mating. Fresh semen was collected from 2 hybrid boars of Yorkshire-Landrace and Yorkshire-Pietrain line and the third boar - a Durocbreed (control) was used to stimulate the sows into oestrus and mate them naturally. Landrace-Yorkshire had shorter time for semen release than Pietrain-Yorkshire breed at first and second time of collecting the semen. Similarly, live born piglets of artificial insemination served 24% higher than natural mating. Therefore, a well-timed artificial insemination method using fresh semen would improve the number of piglets at parturition.